Análisis financiero a los ingresos de la Lubricadora El Chino Dos en los periodos 2018 y 2019 - Rea Reyes, Erika Noemi (2021)
The present case study entitled FINANCIAL ANALYSIS THE INCOME OF THE EL CHINO DOS LUBRICATOR IN THE 2018 AND 2019 PERIODS has as its main objective to discover within the short and long-term income of the income statement and also of the assets of the statement of financial position the variation of the same, in the mentioned years, in which the liquidity, profitability, indebtedness and activity indices will be used to know how the assets have been managed, verify the real situation, and evaluate the management of those who have been in charge . During the financial analysis, fluctuations were observed that affected 2019 with lower liquidity percentages in relation to the previous period, a situation that is known to Lubricator EL CHINO DOS, information that was disclosed through an interview that was carried out.